The Role of Animation Film Media in Enhancing Vocabulary Mastery among Tenth Graders: A Study in a Public High School in Banten, Indonesia - Falalini, Ivania Tiara; Juniardi, Yudi; Utomo, Dhafid Wahyu (Journal of Linguistics, Literacy, and Pedagogy, 2025)
This study explores the role of animation film media in enhancing English vocabulary mastery among tenth-grade students at a public senior high school in Banten, Indonesia. Employing a quantitative experimental design, the research involved two groups: an experimental class and a control class, each consisting of 37 students selected through cluster random sampling. A set of 30 validated multiple-choice items was administered as both a pre-test and post-test to evaluate students’ vocabulary knowledge before and after the intervention. The findings revealed a significant improvement in the experimental group compared to the control group, as confirmed by statistical analysis. These results indicate that animation films can serve as effective instructional media for vocabulary acquisition by providing engaging and context-rich input. Thus, the use of animation films is recommended as an alternative strategy for teaching English vocabulary, supporting diverse learning styles and fostering active classroom participation.